Effects of task difficulty on visual processing speed - Banh, Ngoc Chi; Scharlau, Ingrid

Safety Assistance Systems for Bicyclists: Toward Empirical Studies of the Dooring Problem - Stratmann, Lukas; Banh, Ngoc Chi; Scharlau, Ingrid; Dressler, Falko (ACM Symposium on Principles of Distributed Computing (PODC 2024), Advanced tools, programming languages, and PLatforms for Implementing and Evaluating algorithms for Distributed systems (ApPLIED 2024))
To reach the goal of zero traffic fatalities a year, one building block is the proposition to develop advanced assistance systems for vulnerable road users (VRUs) such as bicyclists. We focus on the dooring problem, i.e., car doors being opened inattentively in the way of an approaching cyclist. We extended our vehicle to everything (V2X) communication-enabled virtual cycling environment for dooring experiments. Our system extends toolkits that are widely used in the V2X research community. We showcase how such a system may be used to realize and evaluate distributed algorithms for VRU safety solutions such as dooring prevention.

Benefiting from Binary Negations? Verbal Negations Decrease Visual Attention and Balance Its Distribution - Banh, Ngoc Chi; Tünnermann, Jan; Rohlfing, Katharina J.; Scharlau, Ingrid (Frontiers in Psychology)
Negated statements require more processing efforts than assertions. However, in certain contexts, repeating negations undergo adaptation, which over time mitigates the effort. Here, we ask negations hamper visual processing and whether consecutive repetitions mitigate its influence. We assessed the overall attentional capacity and its distribution, the relative weight, quantitatively using the formal Theory of Visual Attention (TVA). We employed a very simple form for negations, binary negations. Negated instructions, expressing the only alternative to the core supposition, were cognitively demanding, resulting in a loss of attentional capacity in three experiments. The overall attentional capacity recovered gradually but stagnated at a lower level than with assertions, even after many repetitions. Additionally, negations distributed the attention equally between target and reference stimulus. Repetitions slightly increased the reference' share of attention. Assertions, on the other hand, shifted the attentional weight towards the target. Few repetitions slightly decreased the bias towards the target, many repetitions increased the bias.

First steps towards real-time assessment of attentional weights and capacity according to TVA - Banh, Ngoc Chi; Scharlau, Ingrid (Abstracts of the 65th TeaP)

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, A.; Singh, Amit; Banh, Ngoc Chi; Richter, B.; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, B. (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: HRI; XAI; negation; understanding; explaining; touch interaction; gesture

Effects of verbal negation on TVA’s capacity and weight parameters - Banh, Ngoc Chi; Scharlau, Ingrid (TeaP 2022 - Abstracts of the 64th Conference of Experimental Psychologists)

Folgen wiederholter Negation auf die Aufmerksamkeit - Banh, Ngoc Chi; Scharlau, Ingrid; Rohlfing, Katharina J. (52. Kongress der Deutschen Gesellschaft für Psychologie)